2002
DOI: 10.1046/j.0933-7407.2001.00690.x
|View full text |Cite
|
Sign up to set email alerts
|

Case Report. Multiple etiology post‐surgery endophthalmitis

Abstract: The case describes a septic endophthalmitis arisen in a convalescence period following surgery of cataract extraction. The infection was due to Staphylococcus aureus and three fungal components, Candida albicans, Candida glabrata and Acremonium kiliense, which were subsequently isolated. A careful and prompt laboratory investigation allowed the clinicians to adjust the antimycotic therapy and attain an excellent clinical result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…A review of the medical literature revealed 19 cases of ophthalmic infections involving C glabrata or T glabrata (Delany CM, et al IOVS 2003; 44:ARVO E-Abstract 1396). [1][2][3][4][5][6][15][16][17][18][19] A disproportionately large number of these cases (9) were endophthalmitis that occurred following PKP (Table 1). [1][2][3][4][5][6][7][8][9] After the first case of post-keratoplasty C glabrata endophthalmitis was reported in 1978, only 2 were reported until 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the medical literature revealed 19 cases of ophthalmic infections involving C glabrata or T glabrata (Delany CM, et al IOVS 2003; 44:ARVO E-Abstract 1396). [1][2][3][4][5][6][15][16][17][18][19] A disproportionately large number of these cases (9) were endophthalmitis that occurred following PKP (Table 1). [1][2][3][4][5][6][7][8][9] After the first case of post-keratoplasty C glabrata endophthalmitis was reported in 1978, only 2 were reported until 1998.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Besides the cases of post-keratoplasty endophthalmitis, C glabrata has been reported in a relatively few isolated cases of keratitis, post-cataract endophthalmitis, and endogenous chorioretinitis (Delany CM, et al IOVS 2003; 44:ARVO E-Abstract 1396). [15][16][17][18][19][20][21] It is not clear why C glabrata is most commonly associated with PKP, but several factors are likely to be important. Fungal infections, on the rise as a whole, are associated with the use of immunosuppression and broad-spectrum antibiotic agents, both of which are used therapeutically in corneal transplant patients.…”
Section: Discussionmentioning
confidence: 99%
“…The initial symptoms of Acremonium endophthalmitis are similar to those of most delayed-onset endophthalmitis, including mild pain, redness, floaters and slightly decreased visual acuity [ 7 - 10 ]. The interval between surgery and endophthalmitis onset ranges from two to six weeks [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The initial presenting symptoms of Acremonium endophthalmitis are similar to those of most delayed-onset fungal endophthalmitis, including mild pain, redness, floaters and slightly decreased visual acuity [2-5,7]. The time interval between cataract operation and endophthalmitis ranges from 12 days to six weeks, but is usually one month [2-5,7].…”
Section: Discussionmentioning
confidence: 99%
“…The time interval between cataract operation and endophthalmitis ranges from 12 days to six weeks, but is usually one month [2-5,7]. Interestingly, Acremonium infection may mimic Propionibacterium infection in that both organisms yield similar plaque-like materials in and around the anterior chamber [2-4].…”
Section: Discussionmentioning
confidence: 99%